Artificial Intelligence dan Hak Asasi Manusia: Kajian Hukum tentang Potensi Bahaya di Indonesia - Muh. Akbar Fhad Syahril; A. Darmawansya TL; Murdiono Murdiono; Arini Asriyani (Faculty of Law Andi Sapada Institute of Social Sciences and Business, 2024)
This study examines the potential dangers of Artificial Intelligence (AI) to human rights in Indonesia using a socio-legal approach that combines normative legal analysis and social perspectives. Existing regulations such as the ITE Law and related regulations are inadequate because they do not specifically address human rights protection, accountability, and transparency in the use of AI. Meanwhile, from the social side, AI carries the risk of bias, discrimination, privacy violations, and threats to freedom of expression. Comprehensive regulations and effective law enforcement are needed to ensure the responsible use of AI and respect for human rights in Indonesia.